TEMPORAL SOIL MOISTURE CHANGES UNDER DIFFERENT LAND USES IN THE BRAZILIAN CERRADO - Ayach Anache, Jamil Alexandre; Wendland, Edson Cezar; de Carvalho Diniz Melo, Davi; Sanches de Oliveira, Paulo Tarso; Youlton Millon, Cristian Pablo (Águas Subterrâneas, 2019)
Soil moisture is a key component of the hydrological cycle, which determines runoff generation and groundwater recharge. For the past decades, the Brazilian cerrado has experienced significant loss of its natural landscapes due to pressures of food and energy production (e.g. sugarcane and pasture). Understanding the impacts of such activities on soil moisture is paramount. In this context, three soil moisture sensors were installed in a 30 cm depth in an experimental area. The instruments were placed in different land covers: natural cerrado, pasture and sugarcane. Thus, this study aimed to verify the influence of land cover on the soil moisture monitoring scheme by using observations collected during a period of two years in an experimental area inside Brazilian cerrado biome.